Adventures in problem solving - Shirali, Shailesh (India : Universities press, 2002)
This book deals with an important area in mathematics: Problem Solving, making it an exciting adventure. Having been associated with the Mathematical Olympiad programme since its inception in India, Dr Shailesh Shirali has drawn a lot on this experience in terms of material as well as in terms of the lucid style of writing. In this book, which is addressed to problem buffs, you will find many topics in (3z(Bserious(3y (Band (3z(Brecreational(3y (Bmathematics developed through problems (surds, logarithms, geometry, inequalities, magic squares, cryptarithms, logic, counting, number theory, games such as Nim).s
Includes references and index.
Keywords: Problem solving; Mathematics -- Problems, exercises, etc